The impact of new, renewal and termination sponsorship announcements on share price returns. Issue 4 (1st April 2014) - Kruger, Thomas S; Goldman, Michael; Ward, Mike
Abstract : What impact do sports sponsorship announcements have on the share price returns of sponsoring firms? This research examines the impact of new, renewal and termination sponsorship announcements on returns, employing event study methodology to analyse 118 announcements made by 19 firms over more than 11 years. The mixed findings across all three announcement types indicate the lack of consideration given to sponsorship investment by investors. The findings suggest that, although firms may position their sponsorships so that they contribute towards a competitive advantage, announcements of sports sponsorships are not always taken into account by the market.